Identification of cultivable bacteria in the intestinal tract of Bactrocera dorsalis from three different populations and determination of their attractive potential. Issue 1 (29th May 2013) - Wang, Hongxiu; Jin, Liang; Peng, Tao; Zhang, Hongyu; Chen, Qinglong; Hua, Yuejin
Abstract BACKGROUND This study aimed to identify the cultivable bacteria inhabiting the intestinal tract of adult oriental fruit flies (Bactrocera dorsalis) from laboratory‐reared, laboratory sterile sugar‐reared, and field‐collected populations, and to evaluate the attractiveness of the metabolites produced by the above bacteria to their hosts. RESULTS Fifteen bacterial isolates chosen from the three populations were determined at species level. These 15 strains were cultured and the attractiveness of the whole Luria–Bertani broth, filtered and autoclaved supernatants to B. dorsalis adults was determined using bioassays. The bioassays showed that all bacterial strains were significantly more attractive to B. dorsalis adults than the media‐only control. Among them, Bacillus cereus, Enterococcus faecalis, Enterobacter cloacae and Citrobacter freundii were the most attractive bacteria. Furthermore, results of a subsequent field test showed that the six bacterial strains were significantly more attractive than the control, with B. cereus and E. faecalis attracting significantly more flies. CONCLUSIONS A cultivable bacterial community composed of Enterobacteriaceae, Enterococcaceae, and Bacillaceae was identified in the intestinal tract of B. dorsalis. Metabolites from B. cereus attracted the greatest number of B. dorsalis adults in the laboratory and field. These results provide useful information for the development of bacterial biocontrol agents or implementation as an insecticide. © 2013 Society of Chemical Industry